Repulsion - CARR, JEREMY (Devil's advocates., 2021)
This Devil's Advocate considers Roman Polanski's Repulsion (1965) within the context of familiar horror tropes and the prevailing qualities of Polanski's broader oeuvre. Drawing on concepts of abjection, the 'monstrous-feminine', and the psychology of horror spectatorship, this text focuses on central themes of isolation, sexuality and setting.